BENEFICIATION METHOD AND IRON REMOVAL FROM FELDSPAR ORE - Tinesha, S.; Ismail, I.; Roshaida, A.; Anuar, O.; Voon, C. H. (Journal of Engineering and Technology (JET), 2025)
The sodium feldspar ore from an undisclosed area in Malaysia contains 0.22% potassium oxide and 9.46% sodium oxide, categorizing it as high-quality feldspar ore. It is inapplicable due to high iron content. This research proposed a new effective technique with a two-step process using a magnetic separator and chemical to eliminate iron from feldspar ores. An analysis was performed on the characteristics of sodium feldspar ore, and optimum parameters were identified. The sodium feldspar experienced a substantial decrease in iron oxide concentration, dropping from 2.25% to 0.38%, significantly reducing iron oxide content. This feldspar concentrate fulfils the specifications of the glass and ceramics sectors. The efficient and eco-friendly extraction of feldspar offers a promising method for the sustainable usage of feldspar minerals.